2020
DOI: 10.3389/fpsyg.2020.570216
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Pathways Linking Public Trust During the Coronavirus Pandemic to Mental and Physical Well-being

Abstract: The well-being of the public during the 2019 coronavirus (COVID-19) pandemic is deeply rooted in institutional trust in the government’s risk communication effort. The objective of this study was to examine the psychological pathway through which public trust in the government is associated with mental and physical well-being. We collected cross-sectional data from 501 participants aged ≥18 years using an online panel. Public trust in the government was assessed as our exposure variable. We screened for psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 40 publications
5
29
1
3
Order By: Relevance
“…In support of our first hypothesis, this study confirmed previous research concerning the association between trust in governmental organizations and compliance with public health regulations during the Covid-19 outbreak (Olagoke et al, 2020 ; Sibley et al, 2020 ; Storopoli et al, 2020 ). Indeed, a greater level of trust in political/administrative institutions seems to be one of the strongest predictors of the population’s level of compliance with public health regulations during a pandemic (Blair et al, 2017 ; Rubin et al, 2009 ; Verger et al, 2018 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In support of our first hypothesis, this study confirmed previous research concerning the association between trust in governmental organizations and compliance with public health regulations during the Covid-19 outbreak (Olagoke et al, 2020 ; Sibley et al, 2020 ; Storopoli et al, 2020 ). Indeed, a greater level of trust in political/administrative institutions seems to be one of the strongest predictors of the population’s level of compliance with public health regulations during a pandemic (Blair et al, 2017 ; Rubin et al, 2009 ; Verger et al, 2018 ).…”
Section: Discussionsupporting
confidence: 91%
“…This was a challenging phase of the pandemic as individuals were fatigued and compliance with public health regulations seemed to decrease leading to an increase of infection rates, although the country was less affected in comparison with other EU countries (Bontempi, 2020). In support of our first hypothesis, this study confirmed previous research concerning the association between trust in governmental organizations and compliance with public health regulations during the Covid-19 outbreak (Olagoke et al, 2020;Sibley et al, 2020;Storopoli et al, 2020). Indeed, a greater level of trust in political/administrative institutions seems to be one of the strongest predictors of the population's level of compliance with public health regulations during a pandemic (Blair et al, 2017;Rubin et al, 2009;Verger et al, 2018).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Thus, the way in which the media characterizes public health messages may potentially play a pivotal role in whether the public develop positive or negative reactions to the situation that has evolved around the COVID-19 pandemic. Population mental health and wellbeing may also be influenced by the level of trust people have in their government and health authorities, which in turn may be influenced by media coverage ( 15 ).…”
Section: Introductionmentioning
confidence: 99%